A kind of exterior wall composite board containing fiber reinforced FRC composite material
By generating zirconia on the surface of silicon carbide and organically modifying, the problem of degradation and poor compatibility of acrylate coatings in high-temperature environments is solved, and the mechanical and high-temperature resistance of the coating is significantly improved. It is suitable for a variety of exterior walls Composite board application.
Patent Information
- Application Number
- CN202411418937.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-12
AI Technical Summary
Acrylate coatings are prone to degradation in long-term high temperature environments, and the compatibility of silicon carbide with acrylic resins is poor, which limits its application in composite materials.
Zirconia is generated on the surface of silicon carbide, and organic modification is used to increase its compatibility in the acrylic coating, improve interfacial bonding, and prepare weather-resistant coatings to improve the mechanical properties and high temperature resistance of the coating.
It significantly improves the mechanical properties and high temperature resistance of acrylic weathering coatings, making them exhibit better weathering resistance under extreme climate conditions, and is suitable for a variety of exterior wall applications.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite panels and relates to an exterior wall composite panel containing fiber-reinforced FRC composite materials. Background Art
[0002] The application of inorganic fillers in exterior wall composite panels significantly improves their structural strength, durability and aesthetics, while also giving them excellent thermal insulation properties. By combining different types of fibers and matrix materials, composite panels achieve multiple advantages such as light weight, high strength, and corrosion resistance. Especially in terms of high-temperature resistant exterior wall composite panels, they can effectively ensure the safety of buildings under extreme climatic conditions, extend the service life of buildings, thereby reducing maintenance costs and further improving economic benefits.
[0003] However, although acrylate coatings have good temperature resistance, they are prone to degradation in long-term high temperature environments, which can have an adverse effect on their performance. In addition, silicon carbide, as a material with low density, high strength and excellent thermal insulation properties, has been widely used in many fields. However, silicon carbide has poor compatibility with acrylic resin coating substrates, which limits its application in certain composite materials. Therefore, in practical applications, silicon carbide needs to be organically modified to overcome the compatibility issues between these materials, so as to give full play to their respective advantages. Summary of the invention
[0004] The object of the present invention is to provide an exterior wall composite board containing fiber reinforced FRC composite materials. In the exterior wall composite board, the present invention introduces zirconium oxide to be generated on the surface of silicon carbide in the weather-resistant coating, and increases its compatibility in the acrylic coating through the high temperature resistance of zirconium oxide in silicon carbide and organic modification thereof, improves its interface bonding force with components, significantly improves the mechanical properties and high temperature resistance of the acrylic weather-resistant coating, and makes the exterior wall composite board coated with the coating have better weather resistance; the exterior wall composite board containing fiber reinforced FRC composite materials can be used for: 1. Courtyard fence: replace anticorrosive wood board, PVC board, plastic wood fence, etc.; 2. Building enclosure: replace metal enclosures such as painted iron mesh board and aluminum alloy board; 3. Exterior wall board: replace aluminum alloy, aluminum-plastic board, marble wall board; 4. Outdoor advertising board and building decorative board; 5. Garage door board; 6. Indoor and outdoor decorative board: replace marble and rock board;
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A composite exterior wall panel containing fiber-reinforced FRC composite materials, the composite exterior wall panel consisting of an inner layer, a middle layer, and an outer layer, the inner layer being a plastic honeycomb made of a polymer resin material, the two sides of the inner layer being middle layers, the middle layers being formed by continuous and perpendicular pressing of glass fibers, the outer layer being a weather-resistant coating, the weather-resistant coating being obtained by curing the weather-resistant coating after being treated by a resin feeding device.
[0007] As a preferred technical solution of the present invention, the preparation of the weather-resistant coating comprises the following steps:
[0008] Step S1: after methacrylic acid, methyl methacrylate, hydroxyethyl methacrylate and mixed monomers are uniformly mixed, a solvent is added for preheating, an initiator and a modified filler are added, mixed, and subjected to a constant temperature treatment, and cooled to room temperature to obtain a modified acrylic resin;
[0009] Step S2: after the modified acrylic resin, leveling agent, nanocellulose and additives are uniformly stirred, a solvent is added, heated and stirred, and then sieved to obtain a weather-resistant coating;
[0010] As a preferred technical solution of the present invention, in step S1, the preheating is to raise the temperature to 70-75°C; the constant temperature treatment is to perform constant temperature treatment at 70-76°C for 6-8h.
[0011] As a preferred technical solution of the present invention, in step S1, the mass ratio of methacrylic acid, methyl methacrylate, hydroxyethyl methacrylate, mixed monomer, solvent, initiator and modified filler is 6-8:16-22:7-8:13-15:68-75:0.9-1.2:4.2-4.8.
[0012] As a preferred technical solution of the present invention, in step S1, the mixed monomer is prepared by mixing styrene, N-hydroxymethyl acrylamide and isooctyl acrylate in a mass ratio of 0.8:1.2-1.5:3-4.
[0013] As a preferred technical solution of the present invention, in step S1, the solvent is propylene glycol diacetate; the initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, tert-butyl hydroperoxide and di-tert-butyl peroxide.
[0014] As a preferred technical solution of the present invention, in step S2, the uniform stirring is stirring at a speed of 1200-1300 r / min for 20-30 min; the heating stirring is stirring at a temperature of 30-40°C and a speed of 400-600 r / min for 10-15 min; and the screening is through a 300 mesh sieve.
[0015] As a preferred technical solution of the present invention, in step S2, the mass ratio of the modified acrylic resin, the leveling agent, the nanocellulose, the additive and the solvent is 60-65:0.9-1.2:13-15:1-3:40-50.
[0016] As a preferred technical solution of the present invention, in step S2, the leveling agent is BYK-300; the auxiliary agent is white carbon black; and the solvent is propylene glycol diacetate.
[0017] As a preferred technical solution of the present invention, the preparation method of the modified filler comprises the following steps:
[0018] 1) stirring and mixing silicon carbide and sodium hydroxide aqueous solution, filtering and washing, placing in an oven for vacuum drying to obtain prefabricated silicon carbide;
[0019] 2) In a nitrogen environment, prefabricated silicon carbide, zirconyl chloride and deionized water are mixed and then ultrasonically treated, and a sodium hydroxide aqueous solution is slowly added, filtered and washed, and placed in an oven for drying to obtain a mixed filler;
[0020] 3) Add aminothiophenol and initiator to anhydrous ethanol and mix, add methacrylic acid, heat and stir, remove the solvent by rotary evaporation, wash and dry to obtain an intermediate;
[0021] 4) The mixed filler and the intermediate are placed in anhydrous ethanol and mixed evenly, citral is added after ultrasonic treatment, heated and stirred, the solid is filtered out, washed, and dried to obtain a modified filler.
[0022] As a preferred technical solution of the present invention, in step 1), the stirring and mixing is stirring at a speed of 600-700 r / min for 45-60 min; the washing is washing with deionized water until neutral; and the vacuum drying is drying at a temperature of 75-85° C. to constant weight.
[0023] As a preferred technical solution of the present invention, in step 1), the concentration of the sodium hydroxide aqueous solution is 20-25 g / L; the usage ratio of the silicon carbide and the sodium hydroxide aqueous solution is 2.0-2.4 g: 25 mL.
[0024] As a preferred technical solution of the present invention, in step 2), the ultrasonic treatment is performed at a power of 200-300 W for 15-20 min; the amount of sodium hydroxide aqueous solution added is until no precipitation is generated; the washing is performed using deionized water until neutral; and the drying is performed at a temperature of 82-90° C. until constant weight.
[0025] As a preferred technical solution of the present invention, in step 2), the mass ratio of the deionized water, prefabricated silicon carbide and zirconyl chloride is 40:6-8:3.2-3.5.
[0026] As a preferred technical solution of the present invention, in step 3), the mixing is stirring at a speed of 600-800 r / min for 20-30 min; the heating stirring is stirring at a temperature of 40-45°C under 365nm ultraviolet irradiation for 5-6h; the washing is washing 4 times with anhydrous ethanol; and the drying is drying at a temperature of 75-80°C to constant weight.
[0027] As a preferred technical solution of the present invention, in step 3), the mass ratio of aminothiophenol, initiator, anhydrous ethanol and methacrylic acid is 8-10: 0.40-0.43: 30-36: 15-16.
[0028] As a preferred technical solution of the present invention, in step 3), the initiator is photoinitiator-651; and the aminothiophenol is 3-aminothiophenol.
[0029] As a preferred technical solution of the present invention, in step 4), the ultrasonic treatment is ultrasonic treatment at a frequency of 400-500W for 15-20min; the heating and stirring is stirring at a temperature of 60-70°C for 6-8h; and the drying is drying at a temperature of 70-80°C to constant weight.
[0030] As a preferred technical solution of the present invention, in step 4), the mass ratio of anhydrous ethanol, mixed filler, intermediate and citral is 30:10-12:2.8-3.2:4.4-5.0.
[0031] As a preferred technical solution of the present invention, the resin feeding device includes a tank body, a top cover, an air pump and a feeding pipe; the top cover is arranged on the top of the tank body, and a feeding port matched with the top cover is opened on the top of the tank body, and the top cover is used to seal the feeding port, and a discharge port is provided at the lower part of the outer side surface of the tank body, and the discharge port is connected to the inlet of the feeding pipe; one end of the air pump is connected to the tank body, and the air outlet of the air pump is connected to the air inlet of the top cover through an exhaust pipe.
[0032] Beneficial effects of the present invention:
[0033] In the exterior wall composite board of the present invention, zirconium oxide is introduced into the weather-resistant coating to be generated on the surface of silicon carbide. By utilizing the high temperature resistance of zirconium oxide in silicon carbide and organically modifying the zirconium oxide, its compatibility in the acrylic coating is increased, and the interface bonding strength between the zirconium oxide and the components is improved, thereby significantly improving the mechanical properties and high temperature resistance of the acrylic weather-resistant coating, and the exterior wall composite board coated with the coating has better weather resistance. DETAILED DESCRIPTION
[0034] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0035] A composite exterior wall panel containing fiber-reinforced FRC composite materials, the composite exterior wall panel consisting of an inner layer, a middle layer, and an outer layer, the inner layer being a plastic honeycomb made of a polymer resin material, the two sides of the inner layer being middle layers, the middle layers being formed by continuous and perpendicular pressing of glass fibers, the outer layer being a weather-resistant coating, the weather-resistant coating being obtained by curing the weather-resistant coating after being treated by a resin feeding device.
[0036] The resin feeding device includes a tank body, a top cover, an air pump and a feeding pipe; the top cover is arranged on the top of the tank body, and a feeding port matched with the top cover is opened on the top of the tank body, and the top cover is used to seal the feeding port, and a discharge port is arranged at the lower part of the outer side surface of the tank body, and the discharge port is connected to the inlet of the feeding pipe; one end of the air pump is connected to the tank body, and the air outlet of the air pump is connected to the air inlet of the top cover through an exhaust pipe.
[0037] Specifically, after the weather-resistant paint is fully stirred, it is poured into the tank body and the top cover is closed. After standing for a period of time, the bubbles in the paint will gradually float up and gather on the surface. Then, the air pump is started, and the pressure generated by it is used to make the lower layer of paint flow into the feeding pipe through the discharge port, and finally output through the feeding pipe.
[0038] Example 1
[0039] The preparation of the weather-resistant coating comprises the following steps:
[0040] Step S1: after methacrylic acid, methyl methacrylate, hydroxyethyl methacrylate and a mixed monomer are uniformly mixed, propylene glycol diacetate is added, the temperature is raised to 70°C, an initiator and a modified filler are added and mixed, the mixture is subjected to a constant temperature treatment at 70°C for 6 hours, and the mixture is cooled to room temperature to obtain a modified acrylic resin; wherein the mass ratio of the methacrylic acid, methyl methacrylate, hydroxyethyl methacrylate, the mixed monomer, propylene glycol diacetate, azobisisobutyronitrile and the modified filler is 6:16:7:13:68:0.9:4.2; the mixed monomer is prepared by mixing styrene, N-hydroxymethyl acrylamide and isooctyl acrylate in a mass ratio of 0.8:1.2:3;
[0041] Step S2: After stirring the modified acrylic resin, leveling agent, nanocellulose and white carbon black at a speed of 1200 r / min for 20 minutes, propylene glycol diacetate is added, stirred at a temperature of 30°C and a speed of 400 r / min for 10 minutes, and then passed through a 300-mesh sieve to obtain a weather-resistant coating; the mass ratio of the modified acrylic resin, leveling agent, nanocellulose, additive and propylene glycol diacetate is 60:0.9:13:1:40; the leveling agent is BYK-300 from BYK Chemical.
[0042] Wherein, the preparation method of the modified filler comprises the following steps:
[0043] 1) Stirring silicon carbide and sodium hydroxide aqueous solution at a speed of 600 r / min for 45 minutes, filtering, washing with deionized water until neutral, placing in an oven, and drying at 75° C. to constant weight to obtain prefabricated silicon carbide; the concentration of the sodium hydroxide aqueous solution is 20 g / L; the amount ratio of the silicon carbide to the sodium hydroxide aqueous solution is 2.0 g: 25 mL;
[0044] 2) In a nitrogen environment, prefabricated silicon carbide, zirconyl chloride and deionized water were mixed, ultrasonicated at 200 W for 15 minutes, and sodium hydroxide aqueous solution was slowly added until no precipitate was generated. After filtering, the mixture was washed with deionized water until neutral, placed in an oven, and dried at 82° C. to constant weight to obtain a mixed filler; the mass ratio of the deionized water, prefabricated silicon carbide and zirconyl chloride was 40:6:3.2;
[0045] 3) Adding aminothiophenol and photoinitiator-651 to anhydrous ethanol and stirring at 600 r / min for 20 min, adding methacrylic acid and stirring at 40°C under 365nm ultraviolet irradiation for 5 h, removing the solvent by rotary evaporation, washing with anhydrous ethanol for 4 times, and drying to constant weight at 75°C to obtain an intermediate; the mass ratio of aminothiophenol, photoinitiator-651, anhydrous ethanol and methacrylic acid is 8:0.40:30:15; the aminothiophenol is 3-aminothiophenol;
[0046] 4) The mixed filler and the intermediate are placed in anhydrous ethanol and mixed evenly, and after ultrasonic treatment at a frequency of 400 W for 15 minutes, citral is added and stirred at 60° C. for 6 hours, the solid is filtered out, washed with anhydrous ethanol for 3 times, and dried at 70° C. to constant weight to obtain a modified filler; the mass ratio of the anhydrous ethanol, the mixed filler, the intermediate and the citral is 30:10:2.8:4.4.
[0047] Example 2
[0048] The preparation of the weather-resistant coating comprises the following steps:
[0049] Step S1: after methacrylic acid, methyl methacrylate, hydroxyethyl methacrylate and a mixed monomer are uniformly mixed, propylene glycol diacetate is added, the temperature is raised to 72°C, an initiator and a modified filler are added and mixed, the mixture is subjected to a constant temperature treatment at 72°C for 6.5 hours, and the mixture is cooled to room temperature to obtain a modified acrylic resin; wherein the mass ratio of the methacrylic acid, methyl methacrylate, hydroxyethyl methacrylate, the mixed monomer, propylene glycol diacetate, azobisisobutyronitrile and the modified filler is 6.7:18:7.3:13.7:70:1:4.4; the mixed monomer is prepared by mixing styrene, N-hydroxymethyl acrylamide and isooctyl acrylate in a mass ratio of 0.8:1.3:3.3;
[0050] Step S2: After stirring the modified acrylic resin, leveling agent, nanocellulose and white carbon black at a speed of 1230 r / min for 23 minutes, propylene glycol diacetate is added, and the mixture is stirred at a temperature of 33°C and a speed of 460 r / min for 12 minutes, and then passed through a 300-mesh sieve to obtain a weather-resistant coating; the mass ratio of the modified acrylic resin, leveling agent, nanocellulose, additive and propylene glycol diacetate is 62:1:13.7:1.7:43; the leveling agent is BYK-300 from BYK Chemical.
[0051] Wherein, the preparation method of the modified filler comprises the following steps:
[0052] 1) Stirring silicon carbide and sodium hydroxide aqueous solution at a speed of 630 r / min for 50 min, filtering, washing with deionized water until neutral, placing in an oven, and drying at 78° C. to constant weight to obtain prefabricated silicon carbide; the concentration of the sodium hydroxide aqueous solution is 22 g / L; the amount ratio of the silicon carbide to the sodium hydroxide aqueous solution is 2.1 g: 25 mL;
[0053] 2) In a nitrogen environment, prefabricated silicon carbide, zirconyl chloride and deionized water were mixed, ultrasonicated at 230 W for 17 minutes, and sodium hydroxide aqueous solution was slowly added until no precipitate was generated. After filtering, the mixture was washed with deionized water until neutral, placed in an oven, and dried at 85° C. to constant weight to obtain a mixed filler; the mass ratio of the deionized water, prefabricated silicon carbide and zirconyl chloride was 40:6.7:3.3;
[0054] 3) Adding aminothiophenol and photoinitiator-651 to anhydrous ethanol and stirring at a speed of 660 r / min for 23 minutes, adding methacrylic acid and stirring at a temperature of 42° C. and 365 nm under ultraviolet irradiation for 5.5 hours, removing the solvent by rotary evaporation, washing with anhydrous ethanol for 4 times, and drying to constant weight at a temperature of 77° C. to obtain an intermediate; the mass ratio of aminothiophenol, photoinitiator-651, anhydrous ethanol and methacrylic acid is 8.7:0.41:32:15.3; the aminothiophenol is 3-aminothiophenol;
[0055] 4) The mixed filler and the intermediate are placed in anhydrous ethanol and mixed evenly, and after ultrasonic treatment at a frequency of 430 W for 17 minutes, citral is added and stirred at 63° C. for 6.5 hours, the solid is filtered, washed with anhydrous ethanol for 3 times, and dried at 73° C. to constant weight to obtain a modified filler; the mass ratio of the anhydrous ethanol, the mixed filler, the intermediate and the citral is 30:10.7:2.9:4.6.
[0056] Example 3
[0057] The preparation of the weather-resistant coating comprises the following steps:
[0058] Step S1: after methacrylic acid, methyl methacrylate, hydroxyethyl methacrylate and a mixed monomer are uniformly mixed, propylene glycol diacetate is added, the temperature is raised to 73°C, an initiator and a modified filler are added and mixed, the mixture is subjected to a constant temperature treatment at 74°C for 7.5 hours, and the mixture is cooled to room temperature to obtain a modified acrylic resin; wherein the mass ratio of the methacrylic acid, methyl methacrylate, hydroxyethyl methacrylate, the mixed monomer, propylene glycol diacetate, azobisisobutyronitrile and the modified filler is 7.3:20:7.7:14.3:73:1.1:4.6; the mixed monomer is prepared by mixing styrene, N-hydroxymethyl acrylamide and isooctyl acrylate in a mass ratio of 0.8:1.4:3.7;
[0059] Step S2: After stirring the modified acrylic resin, leveling agent, nanocellulose and white carbon black at a speed of 1260 r / min for 27 minutes, propylene glycol diacetate is added, stirred at a temperature of 37°C and a speed of 530 r / min for 13 minutes, and then passed through a 300-mesh sieve to obtain a weather-resistant coating; the mass ratio of the modified acrylic resin, leveling agent, nanocellulose, additive and propylene glycol diacetate is 63:1.1:14.3:2.3:47; the leveling agent is BYK-300 from BYK Chemical.
[0060] Wherein, the preparation method of the modified filler comprises the following steps:
[0061] 1) Stirring silicon carbide and sodium hydroxide aqueous solution at a speed of 660 r / min for 55 min, filtering, washing with deionized water until neutral, placing in an oven, and drying at 82° C. to constant weight to obtain prefabricated silicon carbide; the concentration of the sodium hydroxide aqueous solution is 23 g / L; the amount ratio of the silicon carbide to the sodium hydroxide aqueous solution is 2.3 g: 25 mL;
[0062] 2) In a nitrogen environment, prefabricated silicon carbide, zirconyl chloride and deionized water were mixed, ultrasonicated at 265 W for 18 minutes, and sodium hydroxide aqueous solution was slowly added until no precipitate was generated. After filtering, the mixture was washed with deionized water until neutral, placed in an oven, and dried at 87° C. to constant weight to obtain a mixed filler; the mass ratio of the deionized water, prefabricated silicon carbide and zirconyl chloride was 40:7.3:3.4;
[0063] 3) Adding aminothiophenol and photoinitiator-651 to anhydrous ethanol and stirring at 730 r / min for 27 min, adding methacrylic acid and stirring at 43° C. under 365 nm ultraviolet irradiation for 5.5 h, removing the solvent by rotary evaporation, washing with anhydrous ethanol for 4 times, and drying to constant weight at 78° C. to obtain an intermediate; the mass ratio of aminothiophenol, photoinitiator-651, anhydrous ethanol and methacrylic acid is 9.3:0.42:34:15.7; the aminothiophenol is 3-aminothiophenol;
[0064] 4) The mixed filler and the intermediate are placed in anhydrous ethanol and mixed evenly, and after ultrasonic treatment at a frequency of 460 W for 18 minutes, citral is added and stirred at 67° C. for 7.5 hours, the solid is filtered, washed with anhydrous ethanol for 3 times, and dried at 77° C. to constant weight to obtain a modified filler; the mass ratio of the anhydrous ethanol, the mixed filler, the intermediate and the citral is 30:11.3:3.1:4.8.
[0065] Example 4
[0066] The preparation of the weather-resistant coating comprises the following steps:
[0067] Step S1: after methacrylic acid, methyl methacrylate, hydroxyethyl methacrylate and a mixed monomer are uniformly mixed, propylene glycol diacetate is added, the temperature is raised to 75°C, an initiator and a modified filler are added and mixed, the mixture is subjected to a constant temperature treatment at 76°C for 8 hours, and the mixture is cooled to room temperature to obtain a modified acrylic resin; wherein the mass ratio of the methacrylic acid, methyl methacrylate, hydroxyethyl methacrylate, the mixed monomer, propylene glycol diacetate, azobisisobutyronitrile and the modified filler is 8:22:8:15:75:1.2:4.8; the mixed monomer is prepared by mixing styrene, N-hydroxymethyl acrylamide and isooctyl acrylate in a mass ratio of 0.8:1.5:4;
[0068] Step S2: After stirring the modified acrylic resin, leveling agent, nanocellulose and white carbon black at a speed of 1300 r / min for 30 minutes, propylene glycol diacetate is added, stirred at a temperature of 40°C and a speed of 600 r / min for 15 minutes, and then passed through a 300-mesh sieve to obtain a weather-resistant coating; the mass ratio of the modified acrylic resin, leveling agent, nanocellulose, additive and propylene glycol diacetate is 65:1.2:15:3:50; the leveling agent is BYK-300 from BYK Chemical.
[0069] Wherein, the preparation method of the modified filler comprises the following steps:
[0070] 1) Stirring silicon carbide and sodium hydroxide aqueous solution at a speed of 700 r / min for 60 min, filtering, washing with deionized water until neutral, placing in an oven, and drying at 85° C. to constant weight to obtain prefabricated silicon carbide; the concentration of the sodium hydroxide aqueous solution is 25 g / L; the amount ratio of the silicon carbide to the sodium hydroxide aqueous solution is 2.4 g: 25 mL;
[0071] 2) In a nitrogen environment, prefabricated silicon carbide, zirconyl chloride and deionized water are mixed, ultrasonicated at 300 W for 20 minutes, and sodium hydroxide aqueous solution is slowly added until no precipitate is generated. After filtering, the mixture is washed with deionized water until neutral, placed in an oven, and dried at 90° C. to constant weight to obtain a mixed filler; the mass ratio of the deionized water, prefabricated silicon carbide and zirconyl chloride is 40:8:3.5;
[0072] 3) Adding aminothiophenol and photoinitiator-651 to anhydrous ethanol and stirring at 800 r / min for 30 min, adding methacrylic acid and stirring at 45°C for 6 h under 365 nm ultraviolet irradiation, removing the solvent by rotary evaporation, washing with anhydrous ethanol for 4 times, and drying to constant weight at 80°C to obtain an intermediate; the mass ratio of aminothiophenol, photoinitiator-651, anhydrous ethanol and methacrylic acid is 10:0.43:36:16; the aminothiophenol is 3-aminothiophenol;
[0073] 4) The mixed filler and the intermediate are placed in anhydrous ethanol and mixed evenly, and after ultrasonic treatment at a frequency of 500 W for 20 minutes, citral is added and stirred at 70° C. for 8 hours, the solid is filtered out, washed with anhydrous ethanol for 3 times, and dried at 80° C. to constant weight to obtain a modified filler; the mass ratio of the anhydrous ethanol, the mixed filler, the intermediate and the citral is 30:12:3.2:5.0.
[0074] Comparative Example 1
[0075] Compared with Example 3, the difference in Comparative Example 1 is that step 1 is not performed, silicon carbide is used instead of prefabricated silicon carbide, and the other components, preparation steps and parameters are the same.
[0076] Comparative Example 2
[0077] Compared with Example 3, Comparative Example 2 is different in that zirconyl chloride is not used, and the other components, preparation steps and parameters are the same.
[0078] Comparative Example 3
[0079] Compared with Example 3, Comparative Example 3 is different in that aminothiophenol is not used, and the remaining components, preparation steps and parameters are the same.
[0080] Comparative Example 4
[0081] Compared with Example 3, Comparative Example 4 is different in that methacrylic acid is not used, and the other components, preparation steps and parameters are the same.
[0082] Comparative Example 5
[0083] Compared with Example 3, the difference in Comparative Example 5 is that citral is not used, and the remaining components, preparation steps and parameters are the same.
[0084] The weather-resistant coatings prepared in Examples 1-4 and Comparative Examples 1-5 were subjected to the following performance tests, and the test results are shown in Table 1.
[0085] Mechanical properties: The coating sheet was cut into a dumbbell shape with a length of 6 mm and a width of 4 mm, and stretched at 30°C and a stretching rate of 5 mm / min to test the tensile strength.
[0086] Weathering test: The tensile strength of the coating was tested after baking at 150°C for 90 hours;
[0087] Table 1
[0088]
[0089] From the test results in Table 1, it can be seen that compared with Comparative Examples 1-5, the weather-resistant coatings prepared by the present invention in Examples 1-4 have excellent mechanical properties and high temperature resistance. By comparative analysis, it can be seen that in Comparative Example 1, step 1 is not performed), the surface structure of silicon carbide cannot form a concave-convex surface, and its anchoring effect on zirconium oxide is reduced; in Comparative Example 2, no zirconium oxide precipitation is generated in situ on the surface of silicon carbide, and the mechanical properties and high temperature resistance of the coating are reduced; Comparative Examples 3 and 5 lack aminothiophenol and citral, and the amino group and the aldehyde group cannot form a more high temperature stable imine structure. At the same time, they lack a benzene ring structure with high mechanical properties and high temperature resistance, and cannot be well compatible with styrene in the system. They lack methacrylic acid, and the modified filler is physically connected to the system components, resulting in a decrease in performance; Comparative Example 4 lacks methacrylic acid, and the compatibility of the modified filler in the system is reduced, the particle interface bonding force is reduced, and the mechanical properties and thermal stability are reduced.
[0090] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. An exterior wall composite panel containing fiber reinforced FRC composite material, characterized in that: The exterior wall composite panel is composed of an inner layer, an intermediate layer, and an outer layer. The inner layer is a plastic honeycomb made of a polymer resin material. The two sides of the inner layer are intermediate layers. The intermediate layers are made of glass fibers that are continuously pressed perpendicularly to each other. The outer layer is a weather-resistant coating. The weather-resistant coating is obtained by curing the weather-resistant coating after being treated by a resin feeding device. The preparation of the weather-resistant coating includes the following steps: Step S1: after methacrylic acid, methyl methacrylate, hydroxyethyl methacrylate and a mixed monomer are uniformly mixed, a solvent is added for preheating, an initiator and a modified filler are added, mixed, and then a constant temperature treatment is performed, and the mixture is cooled to room temperature to obtain a modified acrylic resin; the mixed monomer is prepared by mixing styrene, N-hydroxymethyl acrylamide and isooctyl acrylate in a mass ratio of 0.8:1.2-1.5:3-4; Step S2: after the modified acrylic resin, leveling agent, nanocellulose and additives are uniformly stirred, a solvent is added, heated and stirred, and then sieved to obtain a weather-resistant coating; Wherein, the preparation method of the modified filler comprises the following steps: 1) Stir and mix silicon carbide and sodium hydroxide aqueous solution, filter and wash, and place in an oven for vacuum drying to obtain prefabricated silicon carbide; the amount ratio of silicon carbide to sodium hydroxide aqueous solution is 2.0-2.4g:25mL; 2) In a nitrogen environment, prefabricated silicon carbide, zirconyl chloride and deionized water are mixed and then subjected to ultrasonic treatment, and a sodium hydroxide aqueous solution is slowly added, filtered and washed, and placed in an oven for drying to obtain a mixed filler; the mass ratio of the deionized water, prefabricated silicon carbide and zirconyl chloride is 40:6-8:3.2-3.5; 3) Adding aminothiophenol and initiator to anhydrous ethanol and mixing, adding methacrylic acid, heating and stirring, removing the solvent by rotary evaporation, washing, and drying to obtain an intermediate; the mass ratio of aminothiophenol, initiator, anhydrous ethanol and methacrylic acid is 8-10:0.40-0.43:30-36:15-16; the heating and stirring is stirring at 40-45°C under 365nm ultraviolet irradiation for 5-6h; the initiator is photoinitiator-651; 4) The mixed filler and the intermediate are placed in anhydrous ethanol and mixed evenly, citral is added after ultrasonic treatment, heated and stirred, solids are filtered out, washed, and dried to obtain a modified filler; the mass ratio of the anhydrous ethanol, the mixed filler, the intermediate and the citral is 30:10-12:2.8-3.2:4.4-5.
0.
2. The exterior wall composite panel containing fiber reinforced FRC composite material according to claim 1, characterized in that: In step S1, the preheating is to raise the temperature to 70-75°C; the constant temperature treatment is to perform constant temperature treatment at 70-76°C for 6-8h.
3. The exterior wall composite panel containing fiber reinforced FRC composite material according to claim 1, characterized in that: In step S1, the mass ratio of methacrylic acid, methyl methacrylate, hydroxyethyl methacrylate, mixed monomer, solvent, initiator and modified filler is 6-8:16-22:7-8:13-15:68-75:0.9-1.2:4.2-4.8; the solvent is propylene glycol diacetate; and the initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, tert-butyl hydroperoxide and di-tert-butyl peroxide.
4. The exterior wall composite panel containing fiber reinforced FRC composite material according to claim 1, characterized in that: In step S2, the uniform stirring is stirring at a speed of 1200-1300 r / min for 20-30 min; the adding of solvent and heating and stirring is stirring at a temperature of 30-40° C. and a speed of 400-600 r / min for 10-15 min; and the sieving is sieving through a 300 mesh sieve.
5. The exterior wall composite panel containing fiber reinforced FRC composite material according to claim 1, characterized in that: In step S2, the mass ratio of the modified acrylic resin, the leveling agent, the nanocellulose, the auxiliary agent and the solvent is 60-65: 0.9-1.2:13-15:1-3:40-50; the leveling agent is BYK-300; the auxiliary agent is white carbon black; the solvent is propylene glycol diacetate.
6. The exterior wall composite panel containing fiber reinforced FRC composite material according to claim 1, characterized in that: In step 1), the stirring and mixing is performed at a speed of 600-700 r / min for 45-60 min; the washing is performed with deionized water until neutral; the vacuum drying is performed at a temperature of 75-85° C. until constant weight; and the concentration of the sodium hydroxide aqueous solution is 20-25 g / L.
7. The exterior wall composite panel containing fiber reinforced FRC composite material according to claim 1, characterized in that: In step 2), the ultrasonic treatment is performed at a power of 200-300 W for 15-20 minutes; the amount of sodium hydroxide aqueous solution added is such that no precipitation is generated; the washing is performed using deionized water until neutral; and the drying is performed at a temperature of 82-90° C. until constant weight.
8. The exterior wall composite panel containing fiber reinforced FRC composite material according to claim 1, characterized in that: In step 3), the mixing is performed by stirring at a speed of 600-800 r / min for 20-30 min; the washing is performed by washing with anhydrous ethanol for 4 times; and the drying is performed at a temperature of 75-80° C. to a constant weight.
9. The exterior wall composite panel containing fiber reinforced FRC composite material according to claim 1, characterized in that: In step 4), the ultrasonic treatment is performed at a frequency of 400-500 W for 15-20 min; the heating and stirring is performed at a temperature of 60-70° C. for 6-8 h; and the drying is performed at a temperature of 70-80° C. to a constant weight.
10. The exterior wall composite panel containing fiber reinforced FRC composite material according to claim 1, characterized in that: The resin feeding device includes a tank body, a top cover, an air pump and a feeding pipe; the top cover is arranged on the top of the tank body, and a feeding port matched with the top cover is opened on the top of the tank body, and the top cover is used to seal the feeding port, and a discharge port is arranged at the lower part of the outer side surface of the tank body, and the discharge port is connected to the inlet of the feeding pipe; one end of the air pump is connected to the tank body, and the air outlet of the air pump is connected to the air inlet of the top cover through an exhaust pipe.
Citation Information
Patent Citations
High-wear-resistance motor carbon brush composite material and preparation method thereof
CN117335233A
Preparation process and production equipment of high-performance modified styrene-butadiene latex
CN118271500A